ANALISIS STRUKTUR ASSET, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN EARNING GROWTH DAN RISIKO STRATEGI SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA. (STUDI PADA SEKTOR INDUSTRI - Putri Gamayanti; Nekky Rahmiyati; Tri Ratnawati (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
The purpose of this study is to analyze the structure of assets, capital structure, firm size against firm value with earnings growth and strategy risk as intervening variables, the results of this research show that the asset structure has no significant effect on earnings growth, asset structure has a significant effect on risk strategy , asset structure has a significant effect on capital structure, asset structure has a significant effect on firm value, capital structure has a significant effect on earnings growth, capital structure has no significant effect on strategy risk, capital structure has a significant effect on firm value, firm size has a significant effect on earnings growth, company size does not have a significant effect on strategy risk, firm size has a significant effect on firm value, earnings growth does not have a significant effect on strategy risk, earnings growth sounds uh significant to firm value, strategy risk does not have a significant effect on firm value.